(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
It is very important to be able to correctly interpret the events taking place in the process of globalization, to analyze each reality based on our national interests and values. For this, our national idea and ideology must be strong. The national idea instilled in the minds and thinking of the young generation not only ensures that they are not influenced by any foreign ideas, but also forms the ability to adequately respond to them, encourages them to respect and preserve our national values.